Produksi Enzim Selulase dari Aspergillus niger Secara Fermentasi dalam Medium Kultur Padat - Sri Wahyu Murni (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2012)
Bioethanol made from lignocellulosic biomass is currently being developed. The main obstacle production of bioethanol from lignocellulosic materials is at the stage of the process of hydrolysis of lignocellulosic material to form sugars. Enzymatic hydrolysis using cellulase enzyme is plagued by an expensive price. In the previous studies have been carried out production of Trichoderma reesei cellulase enzymes,in this research conducted using Aspergillus niger by solid substrate fermentation method. Enzyme production studies conducted in two stages in, there were in the aerated Erlenmeyer flask and rotary drum fermenter (RDF). The results showed that the production of cellulase enzymes in the rice straw substrate has resulted in enzyme activity similar to sawdust from the wood sengon. Water content effect on enzyme activity. The best results were obtained on a substrate of rice straw at 60% moisture content and fermentation time of 6 days, the CMC-ase activity of FP-ase was 0.00229 and 0.00095U /ml respectivelly. The best results in sengon sawdust substrate is reached at 70% moisture content and fermentation time of 7 days, obtained CMC-ase and FP-ase activity 0.00257 and 0.00133 U/ml respectivelly. Productivity of the enzyme in the RDF is similar to the Erlenmeyer flask. At RDF, obtained CMC-ase and FP-ase of 0.00243 and 0.00105 U / ml for rice straw substrate, and 0.00224 and 0.00125 U / ml for sengon sawdust substrate.